Implementasi Teknologi Blockchain Dalam Pengembangan Aplikasi Manajemen Penyaluran Bantuan Sosial Berbasis Web - Arya, Dimas; Suwarno, Muhammad Anno (Fakultas Teknik Universitas Persada Indonesia YAI, 2025)
The distribution of social assistance is a crucial component of the government's efforts to reducepoverty and social inequality. However, the implementation of aid programs often faces issuesrelated to transparency, data security, and the risk of misuse. Blockchain technology, with its abilityto provide a transparent and immutable record of data, offers a potential solution to address theseissues. Blockchain can increase transparency by providing a digital ledger that can be accessed byall relevant parties, without the possibility of data manipulation. The technology also allows forimmutable data logging, thus addressing data security concerns and the risk of misuse. In addition,the use of smart contracts allows for the automation of the aid distribution process in accordancewith predetermined provisions, thereby reducing errors and potential abuse. As such, blockchainoffers a potential solution to increase effectiveness and accountability in the implementation ofsocial assistance programs.